Dynamic Performance of Concrete Considering Initial Stresses and Creep - S. Yu. Savin; M. Z. Sharipov (Железобетонные конструкции)
In accidental design situations, the loading mode of reinforced concrete structures includes two typical stages such as long-term deformation under constant or slowly varying load and dynamic impact. The purpose of the presented research was to reveal the peculiarities of stress-strain state of concrete under two-stage static-dynamic loading caused by an emergency situation. To achieve this purpose, the experimental investigations of concrete specimens in the form of prisms were carried out under different loading modes, including quasi-static and dynamic loading. The influence of the presence or absence of a long-term loading stage was also considered. It was shown that long-term loading at a stress level of 0.6 of the ultimate strength had a positive effect on the strength of concrete both in quasi-static tests and in dynamic loading. The hardening coefficient in quasi-static tests was 1.07 for the first series specimens and 1.10 for the second series specimens. The dynamic hardening was 1.20 for the first series specimens and 1.32 for the second series specimens.